Alstrom Syndrome with Novel ALMS1 Mutations: A Case Report - Liu, Lanrong; Li, Hong; Shi, Lixin (Experimental and Clinical Endocrinology & Diabetes Reports, 2017)
Objective To report novel mutations of ALMS1 and evaluate clinical characteristics in the Chinese Child with Alstrom syndrome (ALMS).Methods The Child and his parents were examined clinically and venous blood was collected. ALMSl gene analysis was carried out using DNA Sanger sequencing. Using polymerase chain reaction (PCR) amplified ALMS1 gene exons and splice sequence. The objective products were directly sequenced and analyzed. Pathogenic gene mutations were identified by contrast with the transcript (GRCh37/hg19).Results The Child had typical clinical features of Alstrom syndrome. Sequencing the ALMS1 gene confirmed 2 novel heterozygous non-sense mutations in exon8, c.4600C>T (p.Q1534X) and in exon16, c.11410C>T (p.R3804X), respectively, resulting in premature protein truncation.Conclusions 2 novel heterozygous non-sense mutations were identified in the Chinese Child with Alstrom syndrome, expanding the ALMS1 gene mutations causing Alstrom syndrome.